Pair Taping for Undergraduate EFL Students’ Speaking Fluency and Self Confidence - Syamdianita Syamdianita; Nurhijrah Ismail; Dedi Rahman Nur (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
The need for speaking mastery in English has been dramatically increasing because of the confirmed position of English as a language for international communication. Unfortunately, most of students get less of appreciation in classroom speaking activities. Therefore, to establish a natural approach where students could develop L2 fluency more effectively than what has occurred inside the classroom, the researchers tried Pair Taping (PT) in their Speaking Class. A number of studies have indicated that using PT facilitate students’ fluency and confidence (Washburn & Christianson: 1996, Kubo: 2009, Kluge & Taylor: 2000, and Nguyen: 2012). This current study attempted at answering the questions related to: 1) the potential benefit of PT upon the students’ speaking fluency, 2) the students’ perspectives on their English speaking performance, and 3) the students’ attitudes toward PT. The findings revealed that pair taping could be conducive to promote students’ speaking fluency along with developing their knowledge of language. It also advances our understanding of how pair taping makes contribution to foreign language learning and provide useful insight to teachers, lecturers or course designers in designing speaking course. The implementation of this study was found to be helpful in building up students’ speaking skills by offering innovative learning experience to students.